The Effect of Strawberry (Fragaria ananassa) Extract Concentration as Coagulant on Physical and Chemical Characteristic Fresh Cheese - Eka Wulandari; Ellin Harlia; Mayang Chantika Permatasari (Fakultas Peternakan, Universitas Padjadjaran, 2021)
Cheese is one of the processed products originating from milk which is mostly imported from other countries. Fresh cheese is a soft cheese without ripening process. Protease is one of the important enzymes in cheese making industry, which catalyst to hydrolyze peptide bonds. The purpose of this study was to study the physical and chemical characteristics of fresh cheese at several concentrations of strawberry extract as a coagulant. The study was conducted using a completely randomized design (CRD) consisting of three treatments at the concentration level of strawberry extract P1 (20%), P2 (30%), and P3 (40%), with six replications. The data obtained were evaluated using the variance test and to determine the differences between treatments, the Duncan multiple distance test was carried out. The observed variables were yield, water content, milk clotting activity, pH and color of fresh cheese. The results showed that strawberry extract can be used as a coagulant in the manufacture of fresh cheese up to a concentration of 40% with a yield of 23.81%, water content, milk clotting activity 1260.09 SU/mL, pH 5.04 and the color includes L*59, 48, a* 12.67 and b* 17.32.